1998
DOI: 10.1152/ajpgi.1998.275.2.g203
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction pathways mediating CCK-induced gallbladder muscle contraction

Abstract: The signal transduction that mediates CCK-induced contraction of gallbladder muscle was investigated in the cat. Contraction was measured by scanning micrometry in single muscle cells isolated enzymatically with collagenase. Production ofd- myo-inositol 1,4,5-trisphosphate (IP3) and sn-1,2-diacylglycerol (DAG) was quantitated using HPLC and TLC, respectively. Protein kinase C (PKC) activity was determined by measuring the phosphorylation of a specific substrate peptide from myelin basic protein, Ac-MBP-(4—14).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 32 publications
3
37
0
Order By: Relevance
“…This tendency was similar to that of the degree of inhibition by acidosis of contractile responses to histamine and PGE2. Therefore, a protein kinase C-mediated pathway is involved in agonist-induced contraction, which agrees with a recent report showing that cholecystokinininduced gallbladder contraction is mediated by protein kinase C activation (11).…”
Section: Plasmalemmal Casupporting
confidence: 92%
“…This tendency was similar to that of the degree of inhibition by acidosis of contractile responses to histamine and PGE2. Therefore, a protein kinase C-mediated pathway is involved in agonist-induced contraction, which agrees with a recent report showing that cholecystokinininduced gallbladder contraction is mediated by protein kinase C activation (11).…”
Section: Plasmalemmal Casupporting
confidence: 92%
“…However, it has also been reported that ET-1 can activate G i/o proteins (Kasuya et al, 1992;Kimura et al, 1999). It has been suggested that agonist-induced contraction caused the production of IP 3 via a PTX-sensitive G protein-coupled PLC, and this signaling mechanism might be involved in the generation of contractile responses (Yu et al, 1998;An et al, 1999). Chan et al (2000) reported that enhancement of G q -dependent signals by G i -coupled receptors required activated PLC-␤ and was mediated via the ␤␥-dimer released from the G i .…”
Section: Discussionmentioning
confidence: 99%
“…CCK administration in cholesterol gallstone patients is diminished compared with the response of normal subjects to the same treatment (48), suggesting that some gallstone patients might have impaired gallbladder CCK-1R function as well as reduced CCK-1R number and/or CCK-binding capacity to CCK-1Rs (49,50). Because there is impaired smooth muscle contractility in cell isolates from human gallbladders and from animal models with cholesterol gallstones, Behar and colleagues (51)(52)(53) have proposed that the gallbladder contractile mechanisms involve CCK-1R-mediated activation of phospholipase C, leading to signal-transduction decoupling when the sarcolemmas of the smooth muscle cells of the gallbladder are highly enriched in cholesterol. This may be attributed to a cholesterol-dependent decrease in the number of or dysfunction in CCK-1Rs of gallbladder smooth muscle (52), leading to impaired contractility.…”
Section: Discussionmentioning
confidence: 99%